The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2741/1718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of alpha-enolase as an interferon-alpha 2 alpha 1 regulated gene

Abstract: Interferons (IFNs) are multifunctional cytokines that after binding to the cell surface receptor induce the expression of a large number of genes, which in turn, mediate many biological processes including host defense, cell growth control, signaling, and metabolism. Here we show that IFN-alpha activates the mitogen-activated protein kinases (MAPK) ERK1/2 and the transcription factor CREB/ATF-1, which lead to the alpha-enolase (alpha-ENO) gene expression in fibroblasts. Alpha-ENO mRNA accumulation was apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…Although Pla-induced signal transduction pathways have been analyzed in vitro in a few previous reports (19,21,23,24,31,33), the signaling pathways that govern Pla-induced cell migration in vivo have not been studied in detail. It has been shown that Plg/Pla activates ERK1/2 in fibroblasts (20,21,23,24), monocytes (31), and dendritic cells (33). We have previously shown that Plg/Pla activates the MEK/ERK pathway, leading to the expression of the transcription factors c-fos and Egr-1 (20), which in turn promotes a-enolase expression (23,24), an important Plg receptor that mediates monocyte recruitment in vivo (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Pla-induced signal transduction pathways have been analyzed in vitro in a few previous reports (19,21,23,24,31,33), the signaling pathways that govern Pla-induced cell migration in vivo have not been studied in detail. It has been shown that Plg/Pla activates ERK1/2 in fibroblasts (20,21,23,24), monocytes (31), and dendritic cells (33). We have previously shown that Plg/Pla activates the MEK/ERK pathway, leading to the expression of the transcription factors c-fos and Egr-1 (20), which in turn promotes a-enolase expression (23,24), an important Plg receptor that mediates monocyte recruitment in vivo (14).…”
Section: Discussionmentioning
confidence: 99%
“…1B) in a time-dependent manner. Because we have previously demonstrated that the MEK/ERK pathway is involved in Plg-induced gene expression in fibroblasts and monocytes (20,23,24), and it is known to be involved in cell motility (30), we wondered whether such pathway could underlie the Pla-induced migration in these cells. Interestingly, cell migration was associated with increased phosphorylation of ERK1/2 in both cell types (Fig.…”
Section: Pla-induced In Vitro Cell Migration Is Dependent On Mek/erk mentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analysis for the Ang-(1-7) Mas receptor was performed, as described previously by Sousa et al (30), in periarticular tissues, which include connective soft tissues that surround bone and cartilage and also the synovial membrane, from AIA and control animals. A rabbit polyclonal anti-Mas Ab (Novus Biologicals, Littleton, CO) was used at the dilution of 1:1000.…”
Section: Mas Expression In Articular Tissuesmentioning
confidence: 99%